Peran Minat Membaca dalam Meningkatkan Keterampilan Berbicara Siswa Sekolah Menengah Atas - Wijdan, Muhammad Hibban (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the effect of reading interest on speaking skills in grade XI students of SMA Negeri 1 Gamping. This study is a quantitative study with simple linear regression analysis. The population in this study was 140 grade XI students of SMA Negeri 1 Gamping, and a saturated sampling technique was used. Data collection techniques used questionnaires and documentation. The study results showed that reading interest affects speaking skills in grade XI students of SMA Negeri 1 Gamping, with a calculated F value = 6.789 with a significance level of 0.01 <0.05 and an adjusted R-square value of 46%. The implication is that a high reading interest can enrich vocabulary and broader understanding, making it easier to express ideas appropriately. A high reading interest can give birth to a structured mindset and increase self-confidence, fluency, and clarity when speaking in public, which results from mastering vocabulary and sentence structure.